Revision of Calobrachium Gobbi & Azevedo, gen. nov. (Hymenoptera, Bethylidae), with description of seven new Oriental species - Gobbi, Fernanda T.; Azevedo, Celso O. (Zootaxa, 2016)
A new genus, Calobrachium Gobbi & Azevedo, gen. nov. (type species Calobrachium salum Gobbi & Azevedo, sp. nov.) with seven new species, C. luangum sp. nov., C. miticum sp. nov., C. pongum sp. nov., C. salum sp. nov., C. thanum sp. nov., C. trilinum sp. nov., C. vancum sp. nov. are described and figured. New combination is proposed for C. lepidum (Terayama, 2004), comb. nov. (from Pseudisobrachium Kieffer). A key to species of the genus based on males is given.